2001
DOI: 10.1177/000486580103400306
|View full text |Cite
|
Sign up to set email alerts
|

Deaths in Private and Public Prisons in Australia: A Comparative Analysis

Abstract: Public opinion in Australia has been divided on the question of whether private prisons are welcome and one of the issues in dispute has been the question of whether or not private prisons are associated with proportionately more or fewer deaths of prisoners, particularly suicides, than public prisons. The available evidence is examined, and when the number of deaths, or suicides, per 1000 prisoner years served for all private and public prisons are calculated it is found that the rate for all deaths is signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Much of the written material to date has been written to provide justification for or against the use of private prisons" (p. 27). The literature has discussed the theoretical, ethical, and legal issues surrounding private prisons (Feeley 2002;Harding 1997;Lippke 1997;Reisig and Pratt 2000;Shichor 1998), their cost effectiveness and quality (Logan 1996;Perrone and Pratt 2003;Pratt and Maahs 1999;Schneider 1999), their recidivism rates compared to public prisons LanzaKaduce et al 1999), and even whether there is a difference in death rates (Biles and Dalton 2001;Camp and Gaes 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the written material to date has been written to provide justification for or against the use of private prisons" (p. 27). The literature has discussed the theoretical, ethical, and legal issues surrounding private prisons (Feeley 2002;Harding 1997;Lippke 1997;Reisig and Pratt 2000;Shichor 1998), their cost effectiveness and quality (Logan 1996;Perrone and Pratt 2003;Pratt and Maahs 1999;Schneider 1999), their recidivism rates compared to public prisons LanzaKaduce et al 1999), and even whether there is a difference in death rates (Biles and Dalton 2001;Camp and Gaes 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The answer is that Australia now has by far the highest proportion of its prisoners in private prisons, around 20%, compared with any other country in the world and yet we cannot say with confidence whether they make our justice system better or worse. Many years ago, I was able to show that private prisons produced fewer deaths in custody than government prisons (Biles & Dalton, 2001), and that finding led to further noisy public debate. There is no doubt much more work needs to be done on this subject.…”
Section: Australian Evaluations Of Therapeutic Correctional Programsmentioning
confidence: 99%
“…Most studies focused on the issue of costs rather than conditions and generally found private prisons to be between 4% and 14% less costly to operate than public prisons (Legislative Budget Committee for the State of Washington, 1996;Logan, 1992;Sellers, 1989; Tennessee Select Oversight Committee on Corrections, 1995;Texas Sunset Advisory Commission, 1991). Later studies began to address conditions of confinement and generally found the quality of inmate programming in private facilities to be at least as good as in the public arena (Archambeault & Deis, 1996;Biles & Dalton, 1999;Bottomley, 1996;Culp, 1998;Hatry et al, 1989;Logan, 1992;Sellers, 1989).…”
Section: Proprivatization Advocacy Coalitionmentioning
confidence: 99%